Analysis of Banking Financial Ratio Before and During Covid-19 Pandemi - Eka Sutisna Suryadi; Muhaimin; Lukman Achmad; Dwi Ihsani Febriani (Yayasan Ilomata, 2023)
This research aims to find out if there are differences in the Current Ratio, Debt to Asset Ratio, and Return on Asset to the financial performance of Bank Muamalat Indonesia before and during the Covid-19 pandemic period. The population in this study is the entire financial statements of Bank Muamalat Indonesia and the sample in this study is the financial statements of Bank Muamalat Indonesia period 2017-2022. Data analysis techniques are carried out using the Normality Test, Homogeneity Test, and the Independent Samples Test.